2010
DOI: 10.1111/j.1365-2842.2010.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and surface EMG activity patterns of masticatory muscles

Abstract: The purpose of this study was to evaluate the influence of age on the electromyographic activity of masticatory muscles. All volunteers were Brazilian, fully dentate (except for Group I - mixed dentition), Caucasian, aged 7-80, and divided into five groups: I (7-12 years), II (13-20 years), III (21-40 years), IV (41-60 years) and V (61-80 years). Except for Group V, which comprised nine women and eight men, all groups were equally divided with respect to gender (20 M/20 F). Surface electromyographic records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
7
33

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 28 publications
6
72
7
33
Order By: Relevance
“…The activation pattern eventually increased or decreased, but the numerical pattern changes were small. It should be emphasized that, in agreement with the findings of Cecilio et al, 5 the temporalis muscles were found to be the most active of the muscles studied throughout the experiment. This outcome was not expected in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The activation pattern eventually increased or decreased, but the numerical pattern changes were small. It should be emphasized that, in agreement with the findings of Cecilio et al, 5 the temporalis muscles were found to be the most active of the muscles studied throughout the experiment. This outcome was not expected in our study.…”
Section: Discussionsupporting
confidence: 90%
“…[4][5][6][7][8] The Lucia jig not only eliminates any type of occlusal interference that may cause mandibular deviation of the centric relation (CR) for maximum habitual intercuspation (MHI) but also reduces the effect of muscular hyperactivity. 9 It facilitates the mandibular manipulation of normal subjects, assisting dental surgeons to centralize the condyles along with their respective articular discs in the mandibular fossae.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…In humans, the cross-sectional area and density of the masseter and temporalis muscles decrease as a result of aging (19). Electromyographic (EMG) records in these muscles showed age-related physiological changes which included a reduction in muscle activity (20). Previous studies in humans have indicated a change in chewing function together with a greater number of bites required for mouth movements and bolus formation because of the underlying changes in muscle morphology and physiology with increasing age (19).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, there is a correlation during swallowing between the vertical face dimension, elevators activity, and extent of tooth contact. The activity during swallowing is negatively correlated with the vertical dimension and positively correlated with tooth contact (13,14) . Other authors claim that there is more activity in the masseter muscle during swallowing in the intercuspidal position than in other jaw positions.…”
Section: Discussionmentioning
confidence: 99%